Anatomy and physiology - Shaw, Lin. (UK : Nelson Thornes Ltd., 2005)
Part of a series written for Access to Higher Education students, this book is for those studying for the healthcare professions or biology. It features topics such as circulation and breathing, the nervous system and stress and illness. Learning objectives and summaries appear within each chapter.
Includes index.
Keywords: Human physiology; Human anatomy; Anatomy